A new drought index that considers the joint effects of climate and land surface change. Issue 4 (21st April 2017) - Liu, Meixian; Xu, Xianli; Xu, Chaohao; Sun, Alexander Y.; Wang, Kelin; Scanlon, Bridget R.; Zhang, Lu
Abstract: This study proposes a hydrological drought index, the standardized wetness index (SWI), by combining the structure of the Standardized Precipitation‐Evapotranspiration Index and actual‐evaporation‐based residual water‐energy ratio, in which actual evaporation is estimated using the Budyko hypothesis. The SWI requires three parameters—precipitation, potential evaporation, and parameter n of a Budyko‐type formula. Based on different types of n (fixed or dynamic), SWI can be used to estimate the dryness/wetness resulting from climate change (variability) solely, and from the joint effects of climate and land surface change (variability). Performance of SWI is evaluated using historical droughts and by comparing to the self‐calibrated Palmer Drought Severity Index. Results show that SWI effectively captures global droughts. Furthermore, a case study in two catchments with significant land surface modification indicates that the joint effects of climate and land surface have greater impacts on dryness/wetness in the water‐limited Wuding catchment than in the energy‐limited Poyang catchment. Key Points: Newly developed drought index SWI considers the joint effects of climate and land surface change (variability) SWI has potential to evaluate the impacts of climate and land surface changes (variability) on dryness/wetness Land surface change has larger (less) impacts on drought conditions in water‐limited Wuding (energy‐limited Poyang) catchment